Our climatic environment and pain. Exposure to cold environment at work and the weather in daily life - Farbu, Erlend Hoftun (UiT The Arctic University of Norway, 2021)
Chronic pain is a major health challenge, and musculoskeletal pain is among the main contributors to years lived with disability worldwide. Earlier research found an association between cold exposure at work and musculoskeletal pain. However, the literature is scarce, especially regarding chronic pain. It is a common belief that weather affects pain experience, but the literature on this topic is conflicting, and many researchers have concluded that there is no association. Therefore, the aims of this thesis are to study whether cold exposure at work is associated with chronic pain, and if weather affects pain tolerance. The results indicate that cold exposure at work is a risk factor for chronic pain and musculoskeletal complaints. Those working in a cold environment ≥25% of the time had more chronic pain, and the association was strongest for those who felt cold often. Those working in cold environment ≥25% of the time also had an increased risk of future musculoskeletal complaints. Cold pain tolerance was highest in the winter. There was a non-random variation in pressure pain tolerance. The timescale of this variation was 5.1 days (95% confidence interval: 4.0-7.2), which is similar to that of the meteorological variables studied. Further, both pressure pain tolerance and cold pain tolerance correlated with meteorological variables. These correlations changed over time and temperature and barometric pressure predicted future values of pressure pain tolerance. Taken together, these findings suggest that weather affects pain tolerance in a dynamic non-linear way.